Effectiveness of a system that provides immediate feedback on swimming relay changeover time - Lim, Allysha Yee (Nanyang Technological University, 2023)
Reducing relay changeover times (COTs) is one way to increase a team’s chances of getting a better placing in swimming. Therefore, the Singapore Sports Institute (SSI) developed an Immediate Auditory Feedback (IAF) system to help swimmers reduce their COTs. This study aims to determine the validity of COTs calculated by the system, and to determine the effectiveness of practicing with the IAF system. Elite level national swimmers in Singapore took part in the study. The study consisted of a pre-test, five intervention sessions, and a post-test. Data collected throughout the sessions was used to run a Friedman’s Test, Mann-Whitney U tests, a paired samples t-test, and a correlation. The results of the study showed that a significant difference between the gold standard measurement COTs (GS COTs) and COTs computed by the IAF system was observed, but there was still a strong correlation between the GS COTs and COTs computed by the IAF system. Therefore, COTs computed by the IAF system are concluded to be valid. Additionally, no significant difference was found between the pre-test and post-test COTs for both the Auditory Feedback group (intervention) and the Control group. Thus, it was concluded that the IAF system neither improves, nor does it make swimmers’ COTs worse. Despite this result, this system is advantageous as it is cost-effective, and can be used in collaboration with traditional coaching methods, thus allowing coaches to focus their attention on other aspects of the changeover, like technique.